1997
DOI: 10.1002/(sici)1098-2302(199712)31:4<277::aid-dev5>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Mother and infant smiling exchanges during face‐to‐face interaction in infants with and without Down syndrome

Abstract: We examined social smiling in infants with and without Down syndrome, aged from 3.2 to 13.6 months old. They were videotaped during an episode of spontaneous face-to-face interaction and a subsequent mother's still-face situation. Results indicated that infants smiled longer in the spontaneous face-to-face episode than in the still-face episode, even though this result was only significant in typically developing infants. Typically developing infants also smiled for a longer period than Down's syndrome infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
1
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 0 publications
0
14
1
1
Order By: Relevance
“…Thus, while infants with DS seem to be affected by the still-face Mothers and their infants with DS during the 'still-face' procedure, page 4 episode they may have different emotional responses. These results are compatible with those from a study by Carvajal & Iglesias (1997) who examined smiling during a still-face episode and found that infants with DS showed a small and non-significant reduction during the passive phase. Legerstee & Bowman (1989) examined the looking and smiling responses of eight infants with DS from 8 through to 48 weeks of age during episodes with mother, a stranger, and a puppet.…”
contrasting
confidence: 79%
See 2 more Smart Citations
“…Thus, while infants with DS seem to be affected by the still-face Mothers and their infants with DS during the 'still-face' procedure, page 4 episode they may have different emotional responses. These results are compatible with those from a study by Carvajal & Iglesias (1997) who examined smiling during a still-face episode and found that infants with DS showed a small and non-significant reduction during the passive phase. Legerstee & Bowman (1989) examined the looking and smiling responses of eight infants with DS from 8 through to 48 weeks of age during episodes with mother, a stranger, and a puppet.…”
contrasting
confidence: 79%
“…Thus our prediction was borne out, with infants with DS registering and reacting to an interruption of their engagement with a caregiver. Our findings mirrored those of Legerstee & Bowman (1989) but conflicted with those of Berger & Cunningham, (1986) and Carvajal & Iglesias (1997) who reported no significant effect for smiling for infants with DS of a similar age.…”
Section: Maternal Stylementioning
confidence: 99%
See 1 more Smart Citation
“…However, studies that have investigated the smiling behaviour of children with Down syndrome have found that they follow the same developmental pattern as in typically developing infants, but that there is a delayed emergence of smiling and a shorter duration of smiling during face to face interactions with their mothers than infants who did not have intellectual disabilities (Carvajal & Iglesias, 1997;Berger and Cunningham, 1986). …”
Section: Laughing and Smiling Behaviour In Angelman Syndromementioning
confidence: 91%
“…Los niños trisómicos pueden ser un ejemplo de este tipo de deficiencia construída desde el nacimiento, a partir del mencionado bagaje "insuficiente" (ver, por ejemplo, la excelente exposición de las diferencias estructurales y funcionales del cerebro en Flórez, Troncoso y Diersen, 1996;Flórez, 1999) y de una interacción con el entorno social: irregular, incompleta y a menudo desorganizada, idea ésta corroborada en parte por Carvajal e Iglesias (1997).…”
unclassified